2005
DOI: 10.1016/j.jacc.2005.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdynamic Myocardial Response to Beta-Adrenergic Stimulation in Patients With Chest Pain and Normal Coronary Arteries

Abstract: The present data suggest that an exaggerated myocardial response to beta-adrenergic stimulation plays a role in the mechanisms of chest pain in some patients with normal coronary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
7
0
3
Order By: Relevance
“…10,11 In a study conducted in patients with findings of chest pain and normal coronary arteries, wall motion analysis has shown a LV hypercontractile response to sympathetic stimulation. 12 The same study showed that hypertension was more frequent in patients with hypercontractile response to stress compared with those without hypercontractility. Microneurography and isotope dilution studies of sympathetic activity in hypertensives have shown that increased sympathetic activity and its trophic effects on cardiac muscle are directly related to the development of LVH.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…10,11 In a study conducted in patients with findings of chest pain and normal coronary arteries, wall motion analysis has shown a LV hypercontractile response to sympathetic stimulation. 12 The same study showed that hypertension was more frequent in patients with hypercontractile response to stress compared with those without hypercontractility. Microneurography and isotope dilution studies of sympathetic activity in hypertensives have shown that increased sympathetic activity and its trophic effects on cardiac muscle are directly related to the development of LVH.…”
Section: Introductionmentioning
confidence: 91%
“…LV hypercontractility in the earlier stage of hypertensive heart disease is detectable at rest and under stress in the outpatient setting. [7][8][9][10][11][12]32,58 Recently, it has been demonstrated by comprehensive imaging studies, that LV contractility parameters are blunted by stress in the HFPEF group. 59,60 These findings have consistently correlated with poor prognostic factors of low EF and larger volume under stress.…”
Section: Sympathetic Stimulation and Dynamics In Hypertension-mediatementioning
confidence: 99%
“…Although definitive controlled trials are not available, beta blockers seem to be most effective in reducing the frequency and severity of angina and in improving exercise tolerance [63][64][65][66], and they are considered as first line treatment [6,50]. They may also improve exercise tolerance and decrease symptoms [67].…”
Section: Antianginal Therapymentioning
confidence: 99%
“…LV basal cavity volume is diminished due to prominent LV basal myocardium in real-time 3-dimensional imaging and hypercontractile LV base under stress is the usual finding in hypertension (11,12). Stress-mediated exaggerated hypertension, myocardial hypercontractility and LV outflow gradients or increased intracardiac may be detected in hypertensive patients (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%